2020
DOI: 10.1177/0160017620979611
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Determinants of the Quality of Life in Portuguese Cities

Abstract: The quality of life (QoL) in cities has increasingly been used as a symbol of urban success. Studies addressing this issue tend to focus, however, on large cities and/or on cities from different countries. By using a set of data from a single country, comprehending cities with different population sizes and densities, observations for 11 performance dimensions, and an approach combining the Data Envelopment Analysis (DEA) technique and multivariate regression modeling, this study analyses the QoL of Portuguese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 80 publications
(118 reference statements)
1
14
0
Order By: Relevance
“…For residents, the influencing factors of urban QOL are consistent with the results of previous literature. Rappaport (2007), Albouy (2008Albouy ( , 2013Albouy ( , 2016, Berger et al (2008), Barreira (2020), Zheng, et al (2021), and other scholars have studied urban QOL in U.S., Canadian, Russian, Portuguese, and Chinese cities, and suggested that the climate, education resources, facilities, and environment are the key factors to improve urban QOL [9][10][11][21][22][23][24][25][26][39][40][41]. Due to limits of data availability, we used numbers of hospitals and doctors as a proxy of health care, numbers of college teachers as a proxy of education level, and exclude crime rate, and traffic congestions in city features.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For residents, the influencing factors of urban QOL are consistent with the results of previous literature. Rappaport (2007), Albouy (2008Albouy ( , 2013Albouy ( , 2016, Berger et al (2008), Barreira (2020), Zheng, et al (2021), and other scholars have studied urban QOL in U.S., Canadian, Russian, Portuguese, and Chinese cities, and suggested that the climate, education resources, facilities, and environment are the key factors to improve urban QOL [9][10][11][21][22][23][24][25][26][39][40][41]. Due to limits of data availability, we used numbers of hospitals and doctors as a proxy of health care, numbers of college teachers as a proxy of education level, and exclude crime rate, and traffic congestions in city features.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (2019) measured the QOL in the Chinese city Tianjin and concluded that higher urban QOL is correlated with a shorter distance from the residential place to the central business district and the better urban facilities and environment [21]. Barreira (2020) analyzed the urban QOL in Portugal, and found that the geographical location, population size and density, and the dependence on government public expenditure significantly affected the urban QOL [22]. Chen (2019) and Shi (2021) quantified and ranked the QOL in Chinese cities based on the Rosen-Roback model using both the China Urban Household Survey Data and the 1% Census Data in 2005 [23,24].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Their study pointed out that local economic development promotes the improvement of QoL. Barreira et al (2020) analyzed QoL in Portugal's cities and explored some of its determinants, finding that cities with higher per capita public expenditures exhibit higher QoL levels.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, there are not many examples of specific estimations of QoL in municipalities within specific countries in Europe. Recent examples are [167] for Italy and [163,168] for Portugal. As for Spain, the authors of [169] carried out studies for different regions of the country, and more recently, the authors of [11,170,171] focused on municipalities and cities.…”
Section: An Overview Of Quality Of Lifementioning
confidence: 99%